Determining Sustanaibility Of Urban Settlement In The Center Of City Yogyakarta Indonesia - Pamungkas, Luhur Sapto; Kusumawanto, Arif; Dharoko, Atyanto (International Journal of Science, Technology & Management, 2022)
Urban settlements where urban areas in Indonesia are known as urban villages are one of the distinctive characters of cities in Indonesia, especially in Java. Many urban villages are threatened with sustainability due to the impact of urban development. This research is one of the research models that examines the sustainability of urban villages in Yogyakarta, call it 'kampung kota'. Measurement of sustainability is carried out both from qualitative aspects, namely socio-economic observations, as well as quantitative aspects by measuring the value of Floor Area Ratio (FAR), Energy Consumption Intensity, and Mobility which consists of walkability and bikeability. The conclusion is that urban village life in Yogyakarta currently still has a good level of sustainability, for example in the FAR aspect which is still safe, and the level of mobility is walkable and bikeable. However, the life of the urban village faces a threat of sustainability with the intensity of energy consumption being quite wasteful and several socioeconomic aspects such as environmental conditions, government support, economic stability, and community initiatives. To be able to maintain the sustainability of a number of development efforts are needed to maintain the urban village so that it can remain sustainable.